School choice and segregation: Evidence from Sweden - Anders Böhlmark; Helena Holmlund; Mikael Lindahl (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
This paper studies the evolution of school segregation in Sweden in the aftermath of the 1992 universal school voucher reform, which spurred the establishment of new independent voucher schools and introduced parental choice. The empirical analysis assesses the relative importance of neighbourhood sorting, parental choice and the location of independent schools for school segregation. In particular, it exploits variation in school choice opportunities across municipalities, and provides descriptive evidence that in regions where school choice has become more prevalent, school segregation between immigrants and natives, and between children of high/low educated parents, has increased more than in regions where choice is limited. This result also holds when we account for residential sorting and focus on excess school segregation over and above the segregation that would occur if all pupils attended their assigned schools. The estimates suggest that the increase in school segregation 15 years after the voucher reform that can be attributed to choice is relatively small, and in an international comparison Sweden still ranks as a country with a low-to-medium segregated school system. Our findings are suggestive of the implications for student sorting in other settings where similar voucher schemes are introduced.
Keywords: I20; 330; school segregation; school choice